Contextual Factors and Mastery Motivation in Young Children with and without Cerebral Palsy: A Systematic Review - Hsiang-Han Huang; Hsiang-Han Huang; Tzu-Han Sun; Chia-I Lin; Yi-Ru Chen (Frontiers Media S.A., 2017)
BackgroundMastery motivation is the driving force behind children's desire to explore the surrounding world and their comprehensive development. However, disease factors may lower a child's motivation and hamper development. The aim of this review is to examine mastery motivation in preschool children with cerebral palsy (CP) and the impact of contextual factors on mastery motivation.MethodsSix electronic databases were searched (PubMed, ScienceDirect, Scopus, PsycINFO, Medline, and Airiti Library) using the keywords "Activity," "Cerebral Palsy," "Preschool," "Motivation," "Mastery motivation," "Gross motor," and "Toddler." We reviewed six observational studies and one interventional study for the following features: (1) participants' characteristics; (2) assessment, observation, and intervention methods; (3) findings.ResultsOf the seven studies, three were individual cohort studies and four were individual case-control studies. There were two types of motivation-related measures, standardized measurements and observations of structured tasks or free play. Three studies showed no significant difference in mastery motivation between children with and those without CP when given mental-age-appropriate tasks of moderate difficulty. However, environmental factors including social experience, family interaction, and caregivers' perceptions may affect motivation in preschool children with CP.ConclusionCurrent studies on mastery motivation in preschool children with CP are very limited, and the lack of a universal, theory-based definition of mastery motivation and common assessment frameworks makes it difficult to draw clear conclusions on mastery motivation in children with CP. Future studies should investigate mastery motivation with rigorous study designs to identify ideal activities and environments for preschool children with CP.